THE ANALYSIS OF JAPANESE RESTAURANT’S MARKETING STRATEGIES (Case of Saboten Shokudo Restaurant and Sugoitei Restaurant, Malang) - Akhmad Nizar Dzulkifli (Fakultas Ilmu Administrasi Universitas Brawijaya, 2015)
This study aimed to: (1) Analyze marketing strategy of Japanese Restaurants using SWOT analysis, IFE (Internal Factor Evaluation) and EFE (External Factor Evaluation), (2) Examine marketing strategy appliyed by Japanese Restaurants trough QSPM analysis, (3) Giving the best strategy for Japanese Restaurants through QSPM (Quantitative Strategic Planning Matrix). The type of this research used qualitative approach with matrix data analysis. Research method in this research is descriptive qualitative and data analysis using IFE, EFE, and QSPM matrix. The result of the study reveals that: (1)The finding of the reseach according to both of management in strength, weakness, opportunity, and threat are location of Restaurants is strategic, they just focus on social network to promote their product, high population would increase the purchase activity, and the high price of gasoline would impact in raw material, (2)The alternative strategy for Japanese Restaurant trough QSPM are Product Development and Market Penetration, (3)The best strategy for Japanese Restaurants through QSPM is Product Development. Japanese restaurants in Malang might adoubt this strategy to fight the competition. Therefore, the company is expected to improve and maintain the marketing strategies to cope with the competitors.Key words: Marketing Strategy, EFE (External Factor Evaluation), IFE (Internal Factor Evaluation), SWOT, and QSPMAbstrakTujuan dari penelitian ini adalah: (1)Menganalisis strategi pemasaran Restauran Jepang menggunakan analisis SWOT, IFE (Internal Factor Evaluation) dan EFE (External Factor Evaluation), (2)Membahas strategi pemasaran yang diterapkan Restaurant Jepang melalui analisis QSPM, (3)Memberikan strategi terbaik untuk Restaurant Jepang menggunakan (Quantitative Strategic Planning Matrix). Jenis penelitian ini menggunakan pendekatan kualitatif dengan analisis data IFE, EFE, dan QSPM matrix. Hasil penelitian menunjukkan bahwa: (1)Temuan yang ditemukan dalam penelitian ini berdasarkan kekuatan, kelemahan, peluang, dan ancaman adalah memiliki letak yang strategis, alat promosi hanya mengacu pada jejaring sosial, populasi yang tinggi mempengaruhi aktifitas pembelian, dan naiknya harga BBM mempengaruhi harga bahan baku, (2)Alternatif strategi yang dapat digunakan oleh restoran melalui QSPM adalah pengembangan produk dan penetrasi pasar, (3)Berdasarkan QSPM, alternatif strategi pemasaran terbaik untuk Restoran Jepang di Malang adalah Pengembangan Produk. Restoran Jepang di Malang dapat menggunakan strategi ini untuk menghadapi kompetisi pasar. Maka, perusahaan diharapkan dapat mengembangkan dan membenahi strategi pemasaran agar dapat mengatasi para pesaing.Kata kunci : Strategi Pemasaran, EFE (External Factor Evaluation), IFE (Internal Factor Evaluation), SWOT, dan QSPM